2023
DOI: 10.1186/s12964-023-01076-6
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic Initiation Factor 5A2 localizes to actively translating ribosomes to promote cancer cell protrusions and invasive capacity

Abstract: Background Eukaryotic Initiation Factor 5A (eIF-5A), an essential translation factor, is post-translationally activated by the polyamine spermidine. Two human genes encode eIF-5A, being eIF5-A1 constitutively expressed whereas eIF5-A2 is frequently found overexpressed in human tumours. The contribution of both isoforms with regard to cellular proliferation and invasion in non-small cell lung cancer remains to be characterized. Methods We have eval… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The eukaryotic translation initiation factor 5A (eIF-5A) is an important translation factor found in all eukaryotic organisms. In addition to their regulatory roles in the initiation and elongation of proteins, studies have shown that eIF-5A also contributes to the proliferation, migration and invasive capacity of cancer cells [ 11 , 12 , 13 ]. In T. gondii , eIF-5A is an essential protein for the survival of tachyzoites [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The eukaryotic translation initiation factor 5A (eIF-5A) is an important translation factor found in all eukaryotic organisms. In addition to their regulatory roles in the initiation and elongation of proteins, studies have shown that eIF-5A also contributes to the proliferation, migration and invasive capacity of cancer cells [ 11 , 12 , 13 ]. In T. gondii , eIF-5A is an essential protein for the survival of tachyzoites [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The eIF5A1 isoform is constitutively expressed in all tissues, whereas the eIF5A2 protein shows tissue-specific dependency. The protein level of eIF5A2 has been reported to be too low to be detected in most mammalian cells and tissues [ 8 ], but it is highly expressed in many cancers and it has been proposed as an oncogene [ 8 12 ]. A correlation between increased levels of eIF5A1 and cancer has also been reported and both isoforms have been proposed as biomarkers in several human cancers, including pancreatic ductal adenocarcinoma [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under adverse conditions, eIF5A is involved in the formation of stress granules (SGs) [ 2 ], which are essential structures for the cellular response to stress. Assembly and disassembly of SGs are modulated by different posttranslational modifications including phosphorylation, ubiquitination, poly-ADP ribosylation, arginine methylation, NEDDylation, and SUMOylation [ 12 18 ]. eIF5A can also be regulated through different posttranslational modifications [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%